Evidence of eligibility manipulation for conditional cash transfer programs - Sergio Firpo; Renan Pieri; Euclides Pedroso; André Portela Souza (EconomiA, 2014)
This paper assesses whether eligibility for conditional cash transfer programs has been manipulated, as well as the impact of this phenomenon on time allocation within households. To perform this analysis, we use data from the 2006 PNAD (Brazilian national household survey) and investigate the eligibility manipulation for the Bolsa Família (Family Stipend) program during this time period. The program assists families with a monthly per capita income of around R120.00 (US60.00). By applying the tests developed by McCrary (2008), we find suggestive evidence that individuals manipulate their income by voluntarily reducing their labor supply in order to become eligible to the program. Moreover, the reduction in labor supply is greater among women, especially single or divorced mothers. This evidence raises some concern about the unintended consequences related to the eligibility criteria utilized by Bolsa Família, as well as the program's impact on individuals living in extreme poverty. – – O artigo investiga a manipulaç\~ao para a elegibilidade de programa de transferência condicional de renda bem como se essa manipulaç\~ao se dá através de mudanças da alocaç\~ao do tempo dos membros da família. Para tanto, ele utiliza os dados da Pesquisa Por Amostragem Domiciliar 2006 (PNAD/IBGE) no Brasil e investiga a a manipulaç\~ao para elegibilidade no Bolsa Família. O programa se dirige a famílias com renda per capita familiar inferior a R120 (US 60.00) mensais. utilizando-se os testes desenvolvidos por McCrary (2008), se encontram evidências sugestivas que indivíduos manipulam suas rendas reduzindo voluntariamente sua oferta de trabalho. esta reduç\~ao é maior entre as mulheres solteiras e chefes de família. Estas evidências levantam algumas preocupaç\~oes sobre as consequências n\~ao intencionais dos critérios de elegibilidade do Bolsa Família e dos seus impactos sobre a pobreza e bem estar das famílias.
Keywords: I38; O15; 330; Conditional cash transfers; Brazilian Bolsa Família; Regression discontinuity; Eligibility manipulation